PROFIL EFEK SAMPING PENGGUNAAN ANTIRETROVIRAL PADA PENDERITA HIV/AIDS DI POLIKLINIK VCT DI KOTA MATARAM TAHUN 2019 - Mitha Yunda Pertiwi; Indah Sapta Wardani; A.A Ayu Niti Wedayani (Jurnal Kedokteran, 2020)
Background: In treating HIV infection, Indonesia uses the fast track 90-90-90 approach, which one indicator is giving early ARV treatment to infected patients. First line ARV used in Indonesia today is a fixed-dose combination (FDC) consisting of tenofovir, lamivudine/emtricitabine, and efavirenz. ARV use might cause adverse drug reactions (ADR) with ADR range from mild to severe in HIV patients. This research aims to identify the adverse drug reactions caused by ARV in HIV/AIDS patients in VCT Polyclinic in Mataram City in 2019. Methods: This research is a quantitative descriptive study done in VCT Polyclinic in Mataram city. The subjects are HIV patients in VCT Polyclinic in Mataram city who had met the criteria. This research used secondary data from patients’medical records. Result: Total subjects are 27 patients. ADR occurred in 8 patients (29.6%). These ADR were found in 7 patients using atripla with malaise, dizziness, vomiting, and increased SPOT/SGPT being the most common ADR. One patient using duviral/neviral were found with nausea, vomiting, and itchiness. These ADR came 100% from first degree drug toxicity. Conclusion: The most common ADR were vomiting, malaise, dizziness, and increased SGOT/SGPT. All adverse drug reactions were mild (first degree) therefore therapy was continued and there was no need to consider switching treatment. Keywords: HIV infection, ARV, Atripla, Duviral/Neviral, side effects, first degree